PERANCANGAN SISTEM INFORMASI INVENTORY PENJUALAN SPAREPART BERBASIS WEB MENGGUNAKAN METODE RAD - febi gian benarrivo (Sekolah Tinggi Teknologi Wastukancana, 2023)
Abstract. This research was conducted at CV. Supra Jaya Motor engaged in the Automotive sector. Actually CV. Supra Jaya Motor already has inventory rules for goods sold every day, where the inventory is made to be reported to the Head Office. There are two types of inventory that are carried out, namely Daily and Monthly inventory. Inventory management is very important for achieving performance productivity within the Company in managing goods and stock of goods in the warehouse. One of the main obstacles is in carrying out spare parts sales inventory activities because at this time the running system still has deficiencies such as searching for spare parts information data, recording data, and making reports which take quite a long time because it is done manually so that employees feel hampered in doing work, especially in terms of data collection inventory sales of spare parts.Therefore, researchers propose a solution by creating a system that is able to answer the problems that occur in CV. Supra Jaya Motor, namely making a web-based application that can be accessed by users who have certain access rights. Based on the concept of Rapid Application Development (RAD). In designing the spare parts inventory sales information system, it can help improve time efficiency in collecting data on spare parts that have been sold to customers and provide more accurate and precise information and facilitate reporting of spare parts inventory sales to managers.